Effects of Torrefaction on Carbonization Characteristics of Solid Olive Mill Residue - Cellatoğlu, Nemika; İlkan, Mustafa (College of Natural Resources, 2016)
Torrefaction is an important biomass pretreatment method that impacts fuel characteristics of biomass, specifically during the torrefaction process. Besides improving the fuel characteristics of biomass, torrefaction also contributes to increased quality of liquid and gaseous energy carriers obtained from fast pyrolysis and gasification. In this study, the effect of torrefaction on the solid energy carrier biochar, produced by carbonization, was studied by using solid olive mill residue (SOMR) as raw biomass. The carbonization characteristics of SOMR and torrefied SOMR (tSOMR) were compared by using ultimate and proximate analysis results. The higher heating value (HHV) and energy yields of biochars produced from SOMR and tSOMR were compared. The results showed that torrefaction contributed to the reduction of energy given to the biomass during the carbonization process by decreasing the holding time.
Keywords: Biochar; Biomass; Carbonization; Pretreatment; Solid olive mill residue; Torrefaction